The development of a lateral flow immunochromatographic test strip for measurement of specific IgA and IgG antibodies level against porcine epidemic diarrhea virus in pig milk - Patumporn Jermsutjarit; Dhithya Venkateswaran; Nitaya Indrawattana; Jessada Na Plord; Angkana Tantituvanont; Dachrit Nilubol (Veterinary Quarterly)
Porcine epidemic diarrhea virus (PEDV) causes severe enteric disease and high mortality in neonatal piglets, leading to significant economic losses in the swine industry. Considering that passive lactogenic immunity is crucial for preventing infection in piglets, necessitating a rapid and accurate tool to measure immunity levels. This study aims to develop a lateral flow immunochromatographic strip (LFICS) to assess IgA and IgG antibodies in colostrum and milk, using PEDV S protein. The performance of LFICS was compared to viral neutralization (VN) and enzyme-linked immunosorbent assay (ELISA) as reference methods, with a visual scoring system applied for field monitoring. Colostrum (n = 82) and milk (n = 106) samples were analyzed, showing strong correlation with reference methods and no cross-reactivity with other pig pathogens. The LFICS exhibited high relative sensitivity (Se) and specificity (Sp), with colostrum showing 98.73% Se and 66.67% Sp for IgA, and 96.15% Se and 75.00% Sp for IgG. Milk demonstrated 95.60% Se and 80.00% Sp for IgA, and 84.88% Se and 85.00% Sp for IgG. These findings indicate that the LFICS is a reliable, simple, and rapid method for measuring PEDV-specific IgA and IgG levels, offering valuable support for monitoring herd immunity and evaluating vaccination programs.